First record of Lantanophaga pusillidactylus (Walker, 1864) for the Italian fauna (Lepidoptera Pterophoridae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Lantanophaga pusillidactylus (Walker, 1864) has been found in urban areas; this species is recorded for the first time in Italy (Sicily); it feeds on Lantana camara L. and L. montevidensis (K. Spreng.) Briq
Keywords: Lepidoptera; Pterophoridae; Lantanophaga pusillidactylus; Sicily; new record for Italy; Lantana spp